Análise e reflexão sobre a educação especial inclusiva em Maringá/BR e em Guadalajara /ES - Miranda, Maria de Jesus Cano; Dall'Acqua, Maria júlia Canazza [UNESP]; Heredero, Fladio Sebastián (My University, 2013)
The purpose of this study is to know the route of Special Education in different contexts, the city of Maringa/Brazil and Guadalajara/Spain and analyze the bases underlying the organization, structure and operation of this mode of education having as starting point the process inclusive school. This investigation is based on the theoretical and methodological principles of the historical-cultural notion by Vygotsky. He argues that the existence of fundamental principles underlying the development of children with disabilities. If, on the one hand, the disability imposes limitations on the individual, hindering its development, on the other, just by causing difficulties, enables the movement to compensate, increasing the development of other capabilities. The deficit itself is less. Therefore, it is a field research carried out by means of observations, literature search and document analysis in early childhood education institutions visited in the cities mentioned above. The results showed that there are peculiarities of its path, organization and functioning of Special Education in each of the contexts analyzed. Referentemente the inclusive education movement, it is clear that Spain is a precursor of this process therefore has the right conditions in different ways to conduct the service children with special needs, and on the other hand, schools have the resources and specialized materials they need. While in Brazil the operationalization of these measures occurs more slowly. Thus, we can say that this process of inclusive education does not happen in a linear fashion within mainstream schools and so little action in the different forms of special education in two contexts analyzed.

O objetivo do presente estudo é conhecer o percurso da Educação Especial em contextos distintos, cidade de Maringá/Brasil e Guadalajara/Espanha e analisar as bases que fundamentam a organização, estrutura e o funcionamento dessa modalidade de ensino tendo como ponto de partida o processo de escola inclusiva. Os pressupostos que embasam este trabalho fundamentam-se na concepção Histórico Cultural proposta por Vygotski que defende a existência de princípios essenciais que embasam o desenvolvimento da criança com deficiência. Se, por um lado, a deficiência impõe limitações ao indivíduo, dificultando seu desenvolvimento, por outro, justamente por ocasionar dificuldades, possibilita o movimento para a compensação, ampliando o desenvolvimento de outras capacidades. O déficit em si é o de menos. Portanto, trata-se de uma pesquisa de campo, realizada por meio de observações, pesquisa na literatura e análise documental em instituições de educação infantil visitadas, nas cidades já referidas. Os resultados mostraram que há peculiaridades quanto ao percurso, organização e funcionamento da Educação Especial em cada um dos contextos analisados. Referentemente ao movimento de educação inclusiva, evidencia-se que a Espanha é precursora desse processo, por consequência apresenta condições adequadas nas diferentes formas de conduzir o atendimento às crianças com necessidades especiais, e por outro lado, as escolas dispõem dos recursos humanos e materiais especializados de que necessitam. Enquanto no Brasil a operacionalização dessas medidas ocorre mais lentamente. Assim, podese dizer que esse processo de educação inclusiva não acontece de forma linear dentro das escolas regulares e tão pouco nas diferentes formas de ação da educação especial nos dois contextos analisados.
Special education inclusive in Maringá/BR and Guadalajara/ES
Keywords: Special education; Organization and functioning; Inclusive process; Educação especial; Organização e funcionamento; Processo inclusivo